Impact of Caffeine Consumption on Stress Management and Stamina Among University Students - Suman Bala; Garima Singh; Rashi Arora; Devanshika (Revista Electronica de Veterinaria, 2024)
The most widely consumed psychoactive substance in the world, caffeine is a methylxanthine class stimulant that stimulates the central nervous system (CNS). It is primarily utilized for its nootropic (improving cognitive function), ergogenic (improving physical performance), and eugeroic (promoting wakefulness) qualities. By preventing adenosine from binding to various adenosine receptor types, caffeine inhibits the centrally depressant effects of adenosine and increases acetylcholine release. Because of its three-dimensional structure, which is comparable to adenosine’s, caffeine can bind to and block receptors. In addition, caffeine stimulates the release of calcium from intracellular stores, antagonizes GABA receptors, and raises cyclic AMP levels through nonselective inhibition of phosphodiesterase; however, these effects usually arise at concentrations higher than those normally encountered in human consumption. Caffeine also helps us to relieve stress. Many people like it. It is a neuro-stimulator. According to some researches, it has been proved that it also helps in weight loss if a person is physically active. Research indicates that college students may drink more coffee to help them deal with the pressures and stress of their studies. A large public university’s student body had its relationships between perceived stress and caffeine consumption studied. Students were polled on their perceptions of stress (using Cohen’s Perceived Stress Questionnaire), their views on caffeine, how much they consumed, and how much work they had both inside and outside of the classroom. Both at the start of the semester and again at the midterm, surveys were given out.